The Effect of Acidity and Aging Time in The Synthesis of Al(OH)3 from The Anodized-waste with a Sol-Gel Method - Sri Wardhani; Danar Purwonugroho; Deka Permatasari; Darjito Darjito (Chemistry Department, The University of Brawijaya, 2019)
Synthesis of alumina has been carried out by utilizing anodized waste as raw material. Anodized waste is a by-product of metal anodizing processes such as aluminium. This study aims to determine the effect of acidity (pH) and aging time on the mass of Al(OH)3 and the property of Al(OH)3 as well as Al2O3 that produced. Anodized waste was deposited into Al(OH)3 and then purified. Alumina synthesized by the sol-gel method with pH variations of 7, 8, 9, and 10 and aging times of 24, 48, and 72 hours. The Al(OH)3, which has been produced, was characterized by PSA and powder XRD spectrophotometer. The results showed that the synthesis of Al(OH)3 was influenced by pH and aging time. It affects the yield and particle size of Al(OH)3. The optimum condition of the synthesis was pH 7 and aging time of 24 hours with yield of 1.85 grams. Characterization by PSA at a current diameter of 90% indicate that higher pH value and longer aging time produces smaller particle size. Characterization by powder XRD shows that the Al(OH)3 has gibbsite crystal phase with d values of 3.360, 3.217, 2.252, 2.029, and 1.649 Å.